Nutrient Recovery from Poultry Wastewater by Modified Biochar: An Optimization Study - Lan Thanh, Nguyen; Hang, Vo Thanh; Thuy, Nguyen Thi; Hien, Lam Pham Thanh; Huy*, Nguyen Nhat (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
In this work, we proposed and tested a method for utilizing agricultural waste and alum sludge as an effective adsorbent to treat poultry wastewater. The product was also targeted to be used as fertilizer for agriculture. Modified biochar was produced from crop residues, sludge from a water treatment plant, and magnesium salt. The produced biochar was characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, Brunauer-Emmett-Teller analysis, and X-ray diffraction. The adsorption of ammonia and phosphate in both synthetic and actual poultry wastewater by the produced biochar was conducted. The effect of experimental conditions such as N to P ratio, initial concentrations of ammonium and phosphate, pH, and the amount of biochar on the adsorption capacity for ammonia and phosphate were also investigated. The results from the experiment showed that the best adsorption capacities were 60.64 mgNH4+-N/g and 66.24 mgPO43--P/g, which were produced at the optimum conditions of N to P ratio of 1.25, initial concentration of 90 mg/L, pH 6, and biochar mass of 0.105 g. These results create an opportunity for the effective production of slow-release fertilizer from crop residues and alum sludge for ecological agriculture in the future. Keywords: biochar; adsorption; ammonia; phosphate; crop residues *Corresponding author: Tel.: (+84) 901964985 E-mail: nnhuy@hcmut.edu.vn